Delayed interval delivery of the second twin in a woman with altered markers of inflammation - George Daskalakis; Panagiotis Fotinopoulos; Vasilios Pergialiotis; Mariana Theodora; Panagiotis Antsaklis; Michail Sindos; Nikolaos Papantoniou; Dimitrios Loutradis (BMC, 2018)
Abstract Background Delayed interval intertwin delivery rates are expected to rise during the next years as potent and targeted tocolytic agents are employed and antenatal surveillance methods become more sophisticated and specific in predicting the critical delivery timepoint of optimal perinatal outcome. Case presentation We present a case of delayed intertwin delivery after delivery of the first twin due to premature prelabor rupture of the membranes. Maternal serum White Blood Cells and C-Reactive Protein levels remained high until delivery of the second twin (34 days after the first was delivered), although maternal temperature remained constant. The mother underwent close antenatal surveillance and she was hospitalized. She had an uncomplicated delivery of the second twin at 29+ 2 weeks by cesarean section due to an abnormal Non-Stress Test. Conclusion We strongly suggest future evaluation of maternal serum inflammatory markers among these rare cases as these could predict intraamniotic infection.